PENERAPAN MODEL PEMBELAJARAN EMPIRICAL INDUCTIVE LEARNING CYCLE UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA SMAN 1 GERUNG TAHUN AJARAN 2011/2012 - Agustiarini, Santi (IKIP Mataram, 2013)
This Classroom Action Research was aimed to increase the student’s critical of thinking ability trough Empirical Inductive Learning Cycle. This research was conducted trough five cycles; engagement, exploration, explanation, elaboration, and evaluation. Student’s critical of thinking ability was gained by doing the evaluation on the last cycles. On first cycle the percentages of student’s critical of thinking ability were 75%,68%, 51%, 68%,and 74%; the mean score was 67,64 with classical passing 47%. Furthermore, the mean score of student’s activities was 25,88 in active category. An increasing percentages of each indicator found in the second cycle. They were 76%, 72%, 72%, 83%, and 76%. The mean score was 79,59 with classical passing 92%, and the mean score of student’s learning activities was 31,5 in hyperactive / very active category. The data were obtained from observation, evaluation, and reflection of each cycles. Based on the result, it can be concluded that applying empirical inductive learning cycle in SMAN 1 Gerung was increasing the student’s critical of thinking ability especially to the XI IPA 2 student in academic year 2011/2012.